2007
DOI: 10.1007/s11237-007-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical activation and dehalogenation of freons in low-temperature ionic liquids

Abstract: was studied. It was established in particular that the investigated processes are affected substantially by the electrical conductivity and viscosity of the medium. With decrease of the latter the peak potential in the cyclic voltammetry of the electrochemical reduction of the Freons is shifted toward less negative values while the current increases. It was found that a silver cathode has a specific effect on the electrochemical activation of the Freons in the LTILs, and this may be due to the formation of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Another important factor affecting the process of cathodic activation of the Freons is the material of the electrode. Thus on changing the glassy electrode to silver led to a considerable shift of the peak potential for reduction for both the vicinal and geminal Freons (DE » 0.5-0.8 V) to a less negative field which may be linked with the catalytic properties of Ag in the processes of cathodic activation of halogen-containing compounds [11][12][13][14][15], including the ability of silver atoms at the electrode surface to form complexes (AgLHalLR f ) with the Freon by which breaking of the C-Hal bond is facilitated.…”
Section: Electrochemical Activation and Dehalogenation Of Freons In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor affecting the process of cathodic activation of the Freons is the material of the electrode. Thus on changing the glassy electrode to silver led to a considerable shift of the peak potential for reduction for both the vicinal and geminal Freons (DE » 0.5-0.8 V) to a less negative field which may be linked with the catalytic properties of Ag in the processes of cathodic activation of halogen-containing compounds [11][12][13][14][15], including the ability of silver atoms at the electrode surface to form complexes (AgLHalLR f ) with the Freon by which breaking of the C-Hal bond is facilitated.…”
Section: Electrochemical Activation and Dehalogenation Of Freons In Amentioning
confidence: 99%
“…As shown in papers [13,14,21] the process of electrochemical activation of Freons can be successfully accomplished not only in the traditional media, but also in low temperature ionic liquids which permit the ecological suitability of such reactions and also avoid the necessity of using background salts. In particular, dehalogenation of Freons can be carried out in imidazolium, pyrrolidinium and tetraalkylphosphonium salts, however the high viscosity of the medium decreases the current of the process which is connected to the decreased coefficient of diffusion of the Freon.…”
Section: Electrochemical Activation and Dehalogenation Of Freons In Amentioning
confidence: 99%
“…Titov et al [28][29][30] and Doherty et al [31] have reported findings that pertain to the effects of the reaction medium and cathode material on the reduction of CFC-113. Various lowand room-temperature ionic liquids were investigated and compared to the electrochemical behavior of CFC-113 observed in a conventional DMF-TBABF 4 medium; the higher viscosity and lower conductivity of an ionic liquid cause cathodic peak potentials to be more negative and peak currents to be smaller.…”
Section: A Direct Electrochemical Reduction Of Cfcsmentioning
confidence: 99%
“…Literature relevant to this subject continues to expand at a rapid pace [214][215][216][217][218]. Reports of studies that involve direct or cata-lytic reduction of carbon-halogen bonds in ionic liquids include the following: (a) work by Bhat et al [219] concerning the mechanism of reduction of chloroform in traditional solvents and in an ionic liquid; (b) research by Titov and co-workers [28] and by Doherty et al [31] on the dehalogenation of CFCs in an ionic liquid; (c) a paper [220] describing the nickel(I) salencatalyzed reductions of iodoethane and CFC-113 in 1-butyl-3-methylimidazolium tetrafluoroborate; and (d) a publication by Shen and associates [221], who studied the cobalt(I) salencatalyzed reduction of organic bromides. Several electrochemical studies of the reduction of organic halides in ionic liquids containing CO 2 have been carried out with attractive results from the perspective of remediation [222][223][224][225].…”
Section: Future Directionsmentioning
confidence: 99%
“…These compounds need to be rendered harmless and electrolytic dehalogenation is an attractive route, in particular their conversion to valuable products. We have shown recently that ionic liquids are good media for dehalogenation of C1 and C2 freons 39, 40. Cyclic voltammograms for Freon F114B2 in various ionic liquids (DMF) are shown in Fig.…”
Section: Introductionmentioning
confidence: 98%